Strategi Segmentasi Pasar Produk Mebel di Kecamatan Wonogiri, Kabupaten Wonogiri - Susanti, Christina Esti (Jurnal Widya Manajemen & Akuntansi, 2002)
The purpose of this study is to attempt lo obtain demography characteristic data of the furniture buyers at Subdistrict of Wonogiri, Wonogiri District. The data were used as the basic market segmentation, especially for the company concern wilh marketing mix policies. The primary data were gathered from 40 respondents. There research data were analyzed using cluster analysis, containing Hierarchical Cluster Analysis to determine the amount of the cluste, and Nonhierarchical Cluster Analysis to determine the characteristics of each cluster and members of each of these clusters. The result of this study shows that: l) demography characteristics (income, education, family life cycle, house ownership, and the age of the children's family) used as the basis for market segmentation of furniture product at Wonogiri Subdistrict, Wonogiri District. 2) The potential market for furniture product at Wonogiri Subdistrict, Wonogiri District is the middle income consumers with middle education, in the second generation of family life cycle, the age range of the children is from 5 - 19 , and live in their own house. The characteristics of product that needed for each cluster are a set of furniture, using : raw material from teak, product attribute from foam, the surface of the table was of glass,of medium size, and with plain design. The priority of characteristic product of each cluster is different from one another, so the first cluster of this research consists of raw material and size, the second are size and raw material, and the third are size, raw material, and attribute; and the last is design.